Calidad molinera de la línea promisoria de arroz L-17 (Oryza sp) en la zona de Simón Bolívar, Provincia del Guayas - Castro Valdez, Keyla Ashley (2025)
This research is very important because it provides producers and consumers with data on the quality of new rice varieties. The objective of this study was to analyze the quality of L-17 rice in the province of Guayas, in the Simón Bolívar region. Two types of rice were tested, L-17 and SFL-11, with three replicates of each. The tests were conducted in the FACIAG-UTB Grain Laboratory, which has everything necessary, including a dryer, cleaner, hulling, and polishing equipment. Various parameters were studied, such as: rice hull weight (g), water content (%), whole rice weight (g), milled rice weight (g), rice flour weight (g), broken rice weight (g), whole grain weight (g), and starch and protein percentages (%). The Kruskal-Wallis method, an unconventional approach that evaluated differences in averages, was used for the data analysis. The findings on whole grain rice, measured in grams, show that the L-17 variety weighs more than 606.96 g, representing 60.7% of the whole grain. Regarding the amylose content, the SFL-11 plant type had a percentage of 32.23%, while the L-17 had a level of 30.90%, suggesting that both types have similar amounts of this substance. Regarding protein, the promising L-17 variety averaged 8.30%, compared to 8.50% for the commercial SFL-11 variety, suggesting that there is no significant difference in protein content between the two varieties.